Untangling threads: Rethinking online nursing discussion forums. - Coriasco, Michael; Jones, Jeffrey R.; Hawk, Heather (Teaching & Learning in Nursing, 2025)
• Traditional discussion forums may limit engagement and authentic dialogue. • Student-led discussions promote engagement via peer-driven, flexible conversations. • Student-led discussions promote student autonomy, collaboration, and engagement. Student-led discussions offer an alternative model for online asynchronous discussion forums, shifting facilitation from instructors to students and aligning with universal design for learning (UDL) principles. This study examines students' perceptions of student-led discussions in online nursing education and their effectiveness compared to traditional discussion forums. A qualitative study utilizing reflexive thematic analysis (RTA) to generate themes through analysis of anonymous student feedback about student-led discussions from 2 nursing courses. Four themes were generated: (1) Informal conversations foster authenticity, (2) Collaborative learning through peer interaction, (3) Diverse pathways to learning, and (4) Freedom to express and explore. Students valued the conversational nature of discussions, the opportunity for deeper peer engagement, and the flexibility to explore topics of interest. Findings suggest that student-led discussions enhance student engagement and align with UDL principles, promoting autonomy and meaningful learning experiences. Implementing this approach in nursing education may improve student satisfaction and engagement.